Psychological Abuse in Same-Sex Couples Compared to Heterosexual Couples: Implications for Depression Outcomes - Oravec, Kristyn (2019)
Many studies have documented the mental health repercussions of intimate partner violence (IPV) on heterosexual individuals, with depression being one of the most prevalent outcomes of IPV victimization (Campbell, 2002; Golding, 1999; Mechanic, Weaver, Resick, 2008). There are very few studies that examine the mental health outcomes of IPV within same-sex relationships (Gehring & Vaske, 2017), because much research is rooted in traditional frameworks. In order to bridge gaps in the research, this project will extend work on IPV to focus on LG populations to examine the relationship between recent psychological abuse and mental health outcomes, specifically depression. Participants comprised of 176 community and undergraduate young adults who answered survey questions about sexual orientation, IPV, and depression. Results found that psychological IPV victimization significantly associated with depressive symptoms (β=.55, p<0.001). When examining gender, results indicated that males experienced higher rates of depression when they were victims of psychological IPV (β=-.16, p=0.01). Due to being underpowered, analysis could not adequately examine differences by sexual orientation. Implications of this study suggest a need for more interventions and advocacy for male individuals who are experiencing IPV as many resources are allocated to women and there is less awareness about men as victims